Empirical relationship between electron precipitation and far‐ultraviolet auroral emissions from DMSP observations. Issue 3 (8th March 2013) - Sotirelis, Thomas; Korth, Haje; Hsieh, Syau‐Yun; Zhang, Yongliang; Morrison, Daniel; Paxton, Larry
Abstract: [1] Auroral emissions observed in the far‐ultraviolet wavelength range are compared with measurements of the coincident precipitating electrons and ions that produce the emissions in a large‐scale correlative study. The auroral emissions and particle precipitation are observed with the Special Sensor Ultraviolet Spectrographic Imager and SSJ5 detectors, respectively, both onboard the DMSP F16 satellite. Coincident observations along the same magnetic field line in the Northern Hemisphere are assembled from two consecutive winters (during 2005–2007). A numerical fit to 27, 922 coincident observations provides an empirical relationship between the electron energy flux and the intensity of Lyman‐Birge‐Hopfield long emissions, J E e  = 4.90 ⋅10 8 (eV s –1  sr –1  cm –2 )/R I LBHL (valid in the absence of significant ion fluxes: J E e  > 10 J E ion ). A fit to 1308 coincident observations provides the relationship between the average electron energy and the Lyman‐Birge‐Hopfield short to Lyman‐Birge‐Hopfield long emission ratio, < E e  > = 19.6 keV exp(–2.34 I LBHS / I LBHL ) (valid from 3 to 19.6 keV). These resulting empirical relationships permit the energy flux and average energy of precipitating electrons to be inferred from far‐ultraviolet imagery, in the absence of significant ion precipitation. Key Points: Empirical relationship for electron energy flux using LBHL emissions Empirical relationship for average electron energy using LBHS/LBHL ratio More than 10000 simultaneous observations from DMSP SSJ5 and SSUSI